2016
DOI: 10.5114/pg.2016.57942
|View full text |Cite
|
Sign up to set email alerts
|

The effect of standard therapy on mean platelet volume in patients with chronic hepatitis C

Abstract: IntroductionChronic hepatitis C (CHC) infection is a systemic disorder that can lead to liver inflammation, fibrosis, cirrhosis, and hepatocellular cancer. The mean platelet volume (MPV) is widely used as an inflammatory marker to evaluate the platelet function and the status of systemic inflammation.AimTo determine the pre- and post-treatment MPV values in CHC patients who were administered a 48-week antiviral therapy based on systemic inflammation.Material and methodsWe enrolled 28 patients, diagnosed with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…One of the remarkable features of the study was that the mean MPV of each group was significantly higher than the mean MPV of the control group regardless of cirrhosis etiology. This result was consistent with previous studies on chronic liver diseases, in which the increase in MPV value was correlated with inflammation [24][25][26].Also the results of recent studies by Kurt and Qi are compatible with our data [27][28]. In some previous studies, MPV was found to be lower in patients with hypersplenism than in the control group, and this has been shown to cause from spleen's destruction of large volumed platelets by holding them [21,29].…”
Section: Discussionsupporting
confidence: 93%
“…One of the remarkable features of the study was that the mean MPV of each group was significantly higher than the mean MPV of the control group regardless of cirrhosis etiology. This result was consistent with previous studies on chronic liver diseases, in which the increase in MPV value was correlated with inflammation [24][25][26].Also the results of recent studies by Kurt and Qi are compatible with our data [27][28]. In some previous studies, MPV was found to be lower in patients with hypersplenism than in the control group, and this has been shown to cause from spleen's destruction of large volumed platelets by holding them [21,29].…”
Section: Discussionsupporting
confidence: 93%
“…Whereas, several studies showed that MPV is decreased in HIV-infected patients 30 , 31 , suggesting impaired platelet production rather than increased destruction. In HCV infection, the status of platelet was closely correlated with degree of fibrosis, platelet counts was decreased while MPV was increased in chronic hepatitis C (CHC) patients, especially in those with advanced fibrosis 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%